Corporate philanthropy as a corporate social responsibility component: An Islamic perspective / Wan Noor Hazlina Wan Jusoh … [et al.] - Ismail, Che Zuina; Sulaiman, Noor Hasyimah; Awang, Azarudin (2017)
Nowadays, many companies around the world have great corporate philanthropy as a key component of corporate social responsibility (CSR) programmes. A company that practices CSR embraces responsibility for its actions and, through its activities, positively affects the environment, society, consumers, employees, communities, and other stakeholders. Islamic banks are not alien from this responsibility. Hence, the purpose of this study is to determine the status of corporate philanthropy of Islamic banks from an Islamic perspective. This study is based on Islamic religious values and beliefs according to Shari‘ah, which is the sacred law of Islam derived from the holy Qur‘an and the Prophet‘s hadith. Obviously, it was found that corporate philanthropy is not only consistent with Islamic teaching but also highly recommended for Islamic banks CSR application.